The Book That Can Read Your Mind - Coppo, Marianna (San Francisco : Chronicle Books, 2024)
In this interactive book Lady Rabbit the Magician offers to read your mind, if you pick a member from the magician's audience.
new kids book 2024 spring.
Ages 3 to 5.
Grades K-1.
Keywords: Magicians -- Juvenile fiction; Magic -- Juvenile fiction; Telepathy -- Juvenile fiction; Plot-your-own stories; Plot-your-own stories; Magicians -- Fiction; Magic -- Fiction; Telepathy -- Fiction; Plot-your-own stories; Humorous fiction